Entrepreneurship-Based Programs (EBPs): A Strategy for Community Development in Zimbabwe - et. al., N Munyawarara, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since universally, entrepreneurship-based programs considered as the backbone for community development, this study investigates the relationship between entrepreneurial-based programs and poverty reduction in poor communities in Zimbabwe. Entrepreneurs in urban poor communities are facing a plethora of challenges, such as lack of training and development, financial and technological support and the ability to establish meaningful industries. This paper provides an insight into the impact of supporting entrepreneurial-based programs on the urban poor in Zimbabwe. The study found out that supporting entrepreneurship initiatives contributes to community development